A study on media social usage in IR 4.0 Education among primary school students: Case study in Sekolah Kebangsaan Bandar Baru Sintok - Ahmad Shukri, Norsyahida; Mustafar, Mastora (Universiti Utara Malaysia, 2020)
The use of technology-driven media in teaching and learning is very important in meeting the current needs of the nation in education. This paradigm shift is expected to generate a huge impact on education, especially in public institutes of higher learning where such media technology is regarded as indispensable to both teachers and students. Objective of this study are to explore the level social media usage in learning process among primary school students and to identify the technology media tools that used by the students. Teaching methods may no longer be effective with the existence of a new technology that is the lifestyle of today’s generation. Method of this study is quantitative which used a set of questionnaire that distributed to the students in the school. Findings of this study is focus on the level of social media usage among primary school students. As the result, the researcher found out that the level of media usage in learning process among primary school students are at the moderate.